The integrity crisis in accounting: understanding and preventing fraud - Saidi, Siti Masitah; Yusoff, Ruslaina; Abd Rahman, Shariful Amran (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2024)
In today's challenging times, it is imperative for the accounting profession to maintain integrity and accuracy in order to create trust in financial reporting. However, the most important challenge today is overcoming the prevalence of accounting fraud, which poses a significant challenge. It raises concerns about the reliability of financial information. There are several factors that can be associated with this issue, including the triangle of fraud, ethical dilemmas, lack of ethics, and unfamiliarity with laws and regulations. This article will briefly discuss the nature of accounting fraud, its causes, and the long-term effects on stakeholders in the financial environment. Fraud Triangle Factors According to the fraud triangle theory, three main elements—pressure, opportunity, and rationalization—are among the factors that influence an individual to commit fraud. The pressure often resulting from insurmountable financial problems has created an environment where unethical decisions may seem justified (Oboh, 2023). Personal financial pressures and corporate culture have influenced employees to commit widespread fraud (Tutino & Merlo, 2019). They also found employees facing great pressure to meet unrealistic performance targets have rationalized their actions in an environment that rewards unethical behaviour. Weak internal controls, inadequate supervision, and a lack of audit procedures have created opportunities for fraud (Rifai & Mardijuwono, 2020; Tutino & Merlo, 2019). When individuals perceive a low risk of being caught, they may exploit their position (Munteanu et al., 2024). For example, the WorldCom and Enron cases have illustrated how inadequate internal controls allowed executives to manipulate financial statements without immediate detection (Dimitrijevic et al., 2020). Similarly, the identification of red flags in financial statements is important to prevent fraud, as illustrated in a recent study that emphasizes the importance of vigilance in auditing practices (du Toit, 2024). Ethical Dilemmas